Outcome of femoral neck system for the management of femoral neck fractures - Shaha, Rajon Chandra; Sarker, Manash Chandra; Alam, M. Jahangir; Ahmed, Takvir; Ahmed, Faisal; Hossain, M. Manir; Sengupta, Upal; Hosen, Didar (International Journal of Research in Orthopaedics, 2026)
Background: Femoral neck fractures present significant challenges in orthopedic practice, necessitating effective surgical interventions for optimal recovery. This study aims to evaluate the outcomes of femoral neck fracture fixation using the femoral neck system (FNS). Methods: This quasi-experimental study at National Institute of Traumatology and Orthopedic Rehabilitation (NITOR), Dhaka, Bangladesh, from March 2022 to September 2024 included 45 patients with femoral neck fractures. Patients aged 18-65 years with fractures within 14 days were treated using the FNS after preoperative assessment and prophylactic antibiotics. Postop care involved exercises, progressive weight-bearing, radiographic follow-up, and Harris hip score (HHS) evaluation. Data were analyzed using SPSS 26; ethical approval and informed consent were obtained. Results: In 45 patients undergoing femoral neck fixation with FNS, mean age was 41.8±9.3 years, with 78% males. Road traffic accidents caused 60% of fractures; 53% involved the right femur. Surgery occurred at 4.6±1.8 days post-injury, with a mean hospital stay of 9.6±1.8 days. At final follow-up, 62% reported slight pain, 80% had no limping, and 13% experienced complications. Radiological union was achieved in 96% at 13.3±1.6 weeks. Mean HHS was 86.1±8.8, with 85% showing excellent or good functional outcomes. Conclusions: FNS fixation of femoral neck fractures is a safe and effective approach, yielding high rates of healing, functional recovery, and minimal complications.